2007
DOI: 10.3141/2000-03
|View full text |Cite
|
Sign up to set email alerts
|

Extending Adaptive Cruise Control to Adaptive Driving Strategies

Abstract: An adaptive cruise control (ACC) strategy is presented in which acceleration characteristics, that is, driving styles, automatically adapt to different traffic situations. The three components of the concept are the ACC itself, implemented in the form of a car-following model; an algorithm for the automatic real-time detection of the traffic situation based on local information; and a driving strategy matrix to adapt the driving characteristics–that is, the parameters of the ACC controller–to the traffic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 24 publications
1
67
0
Order By: Relevance
“…This is verified using the IDM. The simulations only included passenger cars, all with a length of 4.5 m. All cars were controlled by an IDM with parameter values according to table 2 in Kesting et al (2007), which e.g. imply a jam distance of 2 m, a desired following time gap of 1.5 s, a maximum acceleration of 1.4 m/s 2 and a desired deceleration of 2 m/s 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This is verified using the IDM. The simulations only included passenger cars, all with a length of 4.5 m. All cars were controlled by an IDM with parameter values according to table 2 in Kesting et al (2007), which e.g. imply a jam distance of 2 m, a desired following time gap of 1.5 s, a maximum acceleration of 1.4 m/s 2 and a desired deceleration of 2 m/s 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous traffic simulation studies of ACC can also be found in the literature (Minderhoud and Bovy, 1999;Hoogendoorn and Minderhoud, 2002;Davis, 2004Davis, , 2007van Arem et al, 2006;Kesting et al, 2007aKesting et al, , 2007b. Traffic simulation has traditionally been applied for quality-of-service analysis of proposed changes in traffic management or road network design.…”
Section: Adaptive Cruise Control and Car-followingmentioning
confidence: 99%
“…In the simulations, parameter values presented by Kesting et al (2007a) have been used for all vehicles, i. e. T d = 1.5 s, a 0 = 1.4 m/s 2 , b = 2 m/s 2 and s 0 = 2 m. For standard vehicles, limited perception and reaction capabilities and anticipation to compensate for these limitations have been taken into account by extending the IDM model with the Human Driver Model (HDM) presented by Treiber et al (2006). HDM is a meta-model that allows modelling of delayed reactions, perception inaccuracies and anticipation of the future traffic situation.…”
Section: Car-following Modelling Of Acc and Human Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…The reader is referred to several good references on traffic and ACC [12][13][14][15][16]. However, I will describe the salient developments as they relate to the present work.…”
Section: Introductionmentioning
confidence: 99%